2013
DOI: 10.4103/0976-237x.114872
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous adenoid cystic carcinoma of maxilla: A rare case report

Abstract: Adenoid cystic carcinoma (ACC) accounts for approximately 6-10% of all salivary gland tumors. Palatal minor salivary glands, parotid, and sub-mandibular glands are usually affected. Rarely, these lesions arising intraosseously have been reported. Mandible is commonly involved than maxilla. The present case is a giant ACC involving the right maxilla. A thorough clinical and radiographic evaluation was performed to assess the involvement of surrounding vital structures along with a meticulous metastatic work-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[ 5 ] In 1979, Batsakis proposed a diagnostic criteria for central salivary gland neoplasm: (1) radiographic evidence of osteolysis, (2) presence of intact cortical plates, (3) presence of intact mucous membrane overlying the lesion, (4) absence of any primary tumor within major or minor salivary gland, (5) histological confirmation of the typical architecture and morphological features of a salivary gland tumor. [ 6 ] In our case, it was thought that the tumor first occurred in the mandible, and later expanded widely throughout the medullary spaces of the mandible.…”
Section: Discussionmentioning
confidence: 75%
“…[ 5 ] In 1979, Batsakis proposed a diagnostic criteria for central salivary gland neoplasm: (1) radiographic evidence of osteolysis, (2) presence of intact cortical plates, (3) presence of intact mucous membrane overlying the lesion, (4) absence of any primary tumor within major or minor salivary gland, (5) histological confirmation of the typical architecture and morphological features of a salivary gland tumor. [ 6 ] In our case, it was thought that the tumor first occurred in the mandible, and later expanded widely throughout the medullary spaces of the mandible.…”
Section: Discussionmentioning
confidence: 75%
“…[ 6 7 ] Krompecher named it as basiloma in 1908. [ 2 ] Later Spies in 1930 and Foote and Frazell in 1953 coined the term “cylindroma.”[ 2 ] They credited the late James Ewing for having used that term for many years. Hence, the tumor has been variously referred to as “cylindroma,” “basiloma,” “adenocystic basaloid carcinoma,” and “adenoepithelioma.”[ 8 ] The term “ACC” is in use till date.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] It accounts for the fifth most common epithelial neoplasm of the salivary glands. [ 2 ] These are clinically innocuous lesions usually characterized by slow evolution, small size, slow growth,[ 3 ] locally invasive growth with high propensity for local recurrence and distant metastasis. [ 4 ] Majority of the cases arise in minor salivary glands, particularly the palate.…”
Section: Introductionmentioning
confidence: 99%
“…These unique pathologic and clinical features mean it is necessary to evaluate the usefulness of 18 F‐FDG PET/CT in patients with ACC of the head and neck (ACCHN) separately from SCC of the head and neck. To our knowledge, the literature contains some case reports, however, few researchers have assessed the clinical impact of 18 F‐FDG PET/CT in patients with ACCHN . Lee et al and Kim et al reported that patients with a high SUVmax had significantly shorter progression‐free survival (PFS) compared with those with a low SUVmax.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the literature contains some case reports, however, few researchers have assessed the clinical impact of 18 F-FDG PET/CT in patients with ACCHN. 19,20 Lee et al 18 and Kim et al 21 reported that patients with a high SUVmax had significantly shorter progression-free survival (PFS) compared with those with a low SUVmax. However, SUVmax is measured using the greatest number of pixels in a region of interest, only showing the highest intensity of 18 F-FDG uptake in the tumor, and is unable to reflect the metabolic activity of the whole tumor.…”
Section: Introductionmentioning
confidence: 99%